Design and Application of Rolling Circle Amplification for a Tumor-Specific Drug Carrier - Kim, Jong Hwan; Jang, Mihue; Kim, Young-Je; Ahn, Hyung Jun (AMER CHEMICAL SOC, 2015)
It is challenging to design rolling circle amplification (RCA) for tumor-selective delivery of drugs. Here, we devise a doxorubicin nanocarrier composed of RCA products, cholesterol-DNA, and folate-DNA conjugates. RCA products, designed to contain tandem repeats of short hairpin DNA, employ the repeated sequences complementary to both DNA conjugates, and thus RCA products/cholesterol-DNA/folate-DNA complexes, generated via sequential base pairing processes, acquire the amphiphilic properties that facilitate self-assembly into the highly condensed nanoparticles (RCA nanoparticles). Doxorubicin-loaded RCA nanopartides, especially with high cargo capacity, release drugs to the environment with the aid of acidity and show selective cytotoxicity to cancer cells. Particularly, the condensed structures enable RCA nanoparticles to be resistant to nucleases in the blood. These results show that RCA nanopartides have great potential as a doxorubicin carrier for targeted cancer therapy, and furthermore, our strategy provides an alternative tool to exploit RCA techniques on drug delivery systems.
Keywords: DNA ORIGAMI; TARGETED TRANSPORT; DELIVERY-SYSTEMS; CANCER-CELLS; NANOPARTICLES; DOXORUBICIN; RESISTANCE; MICROSPONGES; STRATEGIES; THERAPY